Bereavement grief: A population-based foundational evidence study. Issue 7 (9th August 2018) - Wilson, Donna M.; Cohen, Joachim; MacLeod, Rod; Houttekier, Dirk
ABSTRACT: Information is needed on the incidence and prevalence of bereavement grief, and factors associated with severe or prolonged grief. Among 1, 208 representative Canadian adults, 96% had experienced bereavement grief and 78% were actively grieving at interview. Grief levels were higher among women, Protestants, and Catholics, when the death was under 2 years previously, when a spouse, parent, or child had died, and when the perceived death quality was lower. This study reveals the importance of good deaths; they are essential for dying people and also those who mourn their deaths.